The Framing of Dementia in Scientific Articles Published in ‘Alzheimer’s and Dementia’ in 2016 - Kapranov, Oleksandr (East European Journal of Psycholinguistics, 2016)
The present article involves a qualitative study of the framing of dementia in ‘Alzheimer’s and Dementia’, the Journal of the Alzheimer’s Association, published in 2016. The aim of this study is to elucidate how dementia is framed qualitatively in the corpus consisting of scientific articles involving dementia published in ‘Alzheimer’s and Dementia’. The results of the qualitative analysis indicate that dementia is represented in ‘Alzheimer’s and Dementia’ in 2016 as the frames associated with gender, age, costs, caregiver and care-recipients, disability and death, health policy, spatial orientation, medical condition, and ethnic groups. These findings are further discussed in the article.ReferencesAndrews, J. (2011). We need to talk about dementia. Journal of Research in Nursing, 16(5),397–399.Aronowitz, R. (2008). Framing Disease: An Underappreciated Mechanism for the SocialPatterningHealth. Social Science & Medicine, 67, 1–9.Bayles, K. A. (1982). Language function in senile dementia. Brain and language, 16(2),265–280.Bednarek, M. A. (2005). Construing the world: conceptual metaphors and event construals innews stories. Metaphorik.de, 9, 1–27.Brookmeyer, R., Kawas, C. H., Abdallah, N., Paganini-Hill, A., Kim, R. C., & M.M. Corrada(2016). Impact of interventions to reduce Alzheimer’s disease pathology on the prevalence ofdementia in the oldest-old. Alzheimer’s & Dementia, 12(3), 225–232.Burgers, C., Konijn, E., & G. Steen. (2016). Figurative Framing: Shaping Public DiscourseThrough Metaphor, Hyperbole, and Irony. Communication Theory, 26(4)410–430.Carolan, J. (2016). Using a Framing Analysis to Elucidate Learning from a Pedagogy ofStudent-Constructed Representations in Science. In Using Multimodal Representations toSupport Learning in the Science Classroom. Switzerland: Springer.Chen, J. C., Espeland, M. A., Brunner, R. L., Lovato, L. C., Wallace, R. B., Leng, X., Phillips,L.S., Robinson, J.G., Kotchen, J.M., Johnson, K.C., Manson, J. E., Stefanick, M.L., Sato, G.E.,& W.J. Mysiw (2016). Sleep duration, cognitive decline, and dementia risk in older women.Alzheimer’s & Dementia, 12(1), 21–33.Cornejo, R., Brewer, R., Edasis, C., & A.M. Piper (2016). Vulnerability, Sharing, and Privacy:Analyzing Art Therapy for Older Adults with Dementia. In Proceedings of the 19th ACMConference on Computer-Supported Cooperative Work & Social Computing (pp. 1572–1583).ACM.Davis, D. H. (2004). Dementia: sociological and philosophical constructions. Social Science &Medicine, 58(2), 369–378.Delva, F., Touraine, C., Joly, P., Edjolo, A., Amieva, H., Berr, C., Helmer, C., Rouaud, O.,Peres, K., & J. F. Dartigues (2016). ADL disability and death in dementia in a Frenchpopulation-based cohort: New insights with an illness-death model. Alzheimer’s & Dementia,12 (8), 909–916.Entman, R. M. (1993). Framing: Toward clarification of a fractured paradigm. Journal ofCommunication, 43(4), 51–58.Entman, R. M. (2004). Projections of power: Framing news, public opinion, and US foreignpolicy. University of Chicago Press.Entman, R. M. (2007). Framing bias: Media in the distribution of power. Journal ofcommunication, 57(1), 163–173.Gao, S., Ogunniyi, A., Hall, K. S., Baiyewu, O., Unverzagt, F. W., Lane, K. A., Murrell, J. R.,Gureje, O., Hake, A. M., & H. C. Hendrie (2016). Dementia incidence declined in AfricanAmericans but not in Yoruba. Alzheimer’s & Dementia, 12(3), 244–251.Gauthier, S., Albert, M., Fox, N., Goedert, M., Kivipelto, M., Mestre-Ferrandiz, J., &L. T. Middleton (2016). Why has therapy development for dementia failed in the last twodecades?. Alzheimer’s & Dementia, 12(1), 60–64.Gilmour, J. A., & Brannelly, T. (2010). Representations of people with dementia–subaltern,person, citizen. Nursing inquiry, 17(3), 240–247.Green, C. & Zhang, S. (2016). Predicting the progression of Alzheimer’s disease dementia:A multimodal health policy model. Alzheimer’s & Dementia, 12, 776–785.Giudice, D. L., Smith, K., Fenner, S., Hyde, Z., Atkinson, D., Skeaf, L., Malay, R., &L. Flicker (2016). Incidence and predictors of cognitive impairment and dementia in AboriginalAustralians: A follow-up study of 5 years. Alzheimer’s & Dementia, 12(3), 252–261.Górska, S., Forsyth, K., & Maciver, D. (2017). Living With Dementia: A Meta-synthesis ofQualitative Research on the Lived Experience. The Gerontologist, 0, 1–17.Innes, A. (2002). The social and political context of formal dementia care provision. Ageingand Society, 22(04), 483–499.Jensen-Dahm, C., Gasse, C., Astrup, A., Mortensen, P. B., & G. Waldemar (2015). Frequentuse of opioids in patients with dementia and nursing home residents: A study of the entireelderly population of Denmark. Alzheimer’s & Dementia, 11(6), 691–699.Joris, W., d’Haenens, L., & B. Van Gorp. (2014). The euro crisis in metaphors and frames.Focus on the press in the Low Countries. European Journal of Communication, 29(5),608–617.Kapranov, O. (2016). The Framing of Serbia’s EU Accession by the British Foreign Office onTwitter. Tekst i Dyskurs. Text und Diskurs, 9, 67–80.Kaufman, S. R. (1994). Old age, disease, and the discourse on risk: Geriatric assessment in UShealth care. Medical Anthropology Quarterly, 8(4), 430–447.Kunutsor, S., & Laukkanen, J. (2016). Gamma glutamyltranserase and risk of future dementiain middle-aged to older Finnish men: A new prospective cohort study. Alzheimer’s &Dementia, 12, 931–941.Lawless, M., & Augoustinos, M. (2017). Brain health advice in the news: managing notions ofindividual responsibility in media discourse on cognitive decline and dementia. QualitativeResearch in Psychology, 14(1), 62–80.Llorens, F., Schmitz, M., Karch, A., Cramm, M., Lange, P., Gherib, K., Varges, D., Schmidt,C., Zerr, I., & K. Stoeck (2016). Comparative analysis of cerebrospinal fluid biomarkers in thedifferential diagnosis of neurodegenerative dementia. Alzheimer’s & Dementia, 12(5),577–589.Mayeda, E. R., Glymour, M. M., Quesenberry, C. P., & R.A. Whitmer (2016). Inequalities indementia incidence between six racial and ethnic groups over 14 years. Alzheimer’s &Dementia, 12(3), 216–224.Paradis, C. (2010). Good, better and superb antonyms: a conceptual construal approach. Theannual texts by foreign guest professors, 3, 385–402.Parker, J. (2001). Interrogating person-centred dementia care in social work and social carepractice. Journal of Social Work, 1(3), 329–345.Peel, E. (2014). ‘The living death of Alzheimer’s’ versus ‘Take a walk to keep dementia atbay’: representations of dementia in print media and carer discourse. Sociology of health &illness, 36(6), 885–901.Ramirez, J., McNeely, A. A., Scott, C. J., Masellis, M., & S. E. Black (2016). White matterhyperintensity burden in elderly cohort studies: The Sunnybrook Dementia Study, Alzheimer’sThe Framing of Dementia in Scientific Articles Published in Alzheimer’ Disease Neuroimaging Initiative, and Three-City Study. Alzheimer’s & Dementia, 12(2),203–210.Rattinger, G., Fauth, E., Behrens, S., Sanders, C., Schwartz, S., Norton, M. C., Corcoran, C.,Mullins, C. D., Lyketsos, C., & J. T. Tschanz (2016). Closer caregiver and care-recipientrelationships predict lower informal costs of dementia care: The Cache County DementiaProgression Study. Alzheimer’s & Dementia, 12, 917–924.Shash, D., Kurth, T., Bertrand, M., Dufouil, C., Barberger-Gateau, P., Berr, C., Ritchie, K.,Dartigues, J.-F., Begaud, B., Alperovitch, A., & C. Tzourio (2016). Benzodiazepine,psychotropic medication, and dementia: A population-based cohort study. Alzheimer’s &Dementia, 12(5), 604–613.Swacha, K. Y. (2017). Older Adults as Rhetorical Agents: A Rhetorical Critique of Metaphorsfor Aging in Public Health Discourse. Rhetoric Review, 36(1), 60–72.Teipel, S., Babiloni, C., Hoey, J., Kaye, J., Kirste, T., & O.K. Burmeister (2016). Informationand communication technology solutions for outdoor navigation in dementia. Alzheimer’s &Dementia, 12(6), 695–707.Touri, M. & Koteyko, N. (2015). Using corpus linguistic software in the extraction of newsframes: towards a dynamic process of frame analysis in journalistic texts. InternationalJournal of Social Research Methodology, 18(6), 601–616.Van Gorp, B., & Vercruysse, T. (2012). Frames and counter-frames giving meaning todementia: A framing analysis of media content. Social Science & Medicine, 74(8), 1274–1281.Verlinden, V. J., van der Geest, J. N., de Bruijn, R. F., Hofman, A., Koudstaal, P. J., &M. A. Ikram (2016). Trajectories of decline in cognition and daily functioning in preclinicaldementia. Alzheimer’s & Dementia, 12(2), 144–153.Wray, A. (2017). The language of dementia science and the science of dementia language:Linguistic interpretations of an interdisciplinary research field. Journal of Language andSocial Psychology, 36(1), 80–95.Wu, Y. T., Fratiglioni, L., Matthews, F. E., Lobo, A., Breteler, M. M., Skoog, I., & C. Brayne(2016). Dementia in western Europe: epidemiological evidence and implications for policymaking. The Lancet Neurology, 15(1), 116–124.Yuan, J., Zhang, Z., Wen, H., Hong, X., Hong, Z., Qu, Q., Li, H., & J.L. Cummings (2016).Incidence of dementia and subtypes: A cohort study in four regions in China. Alzheimer’s &Dementia, 12(3), 262–271.Zwijsen, S. A., van der Ploeg, E., & C.M. Hertogh (2016). Understanding the world ofdementia. How do people with dementia experience the world?. Internationalpsychogeriatrics/IPA, 1–11.